Implementation of a Healthcare of Elderly Course With Multi-Professional Teachers for Undergraduate Medical Students in a Public University in Malaysia—A Quasi-Experimental Pre and Post Study - Ng, Zhi Ling; Mat Din, Hazwan; Zakaria, Nor Fadhlina; Inche Mat, Liyana Najwa; Wan Zukiman, Wan Zul Haikal; Md Shah, Anim; Daut, Ummi Nadira; Sallehuddin, Hakimah Mohammad (Frontiers in Public Health, 2021)
Clinical practice in the ageing population is changing from organ-specific specialty care to holistic care through comprehensive geriatric assessment and multidisciplinary team management. Hence, we adopted a multi-professional teachers approach in the Healthcare of Elderly Course in a public university in Malaysia. We aimed to analyze the students' attitude, self-perceived competency, and interest in geriatric medicine as a career before and after the course. We also investigate variables that may influence the interest in pursuing a geriatric medicine career among these students. All 96 students in the course were invited to participate in the survey. Sixty-eight (70.8%) completed both pre- and post-course questionnaires. Although most students (93%) have positive attitudes (University of California at Los Angeles Geriatric Attitude Scale >3) towards older adults at baseline, it did not significantly increase post-course. We found that the mean scores for self-perceived competency increased from 3.62 (±0.76) to 3.81 (±0.56) post-course (p<0.01). However, the students remained neutral with no significant change in the mean interest in pursuing a geriatric medicine career after the course. Students with higher self-perceived competency post-course were found to be more interested in geriatric medicine (β=0.56, p<0.001). In conclusion, the HCE course in our centre could sustain a positive attitude and increase self-perceived competency in our students. This is important to increase the preparedness of our graduates in managing older adults with frailty and multimorbidity. Future studies may involve inter-professional education with students from multiple disciplines undergoing the same course to nurture real-life collaborations in managing older people.